Occurrence of near – petal effect on the leaf surface of Annona squamosa - Janairo, Jose Isagani B. (Animo Repository, 2016)
In this paper, we report the presence of densely distributed nanopillar structures with grooved edges on the adaxial leaf surface of Annona squamosa. The hierarchical roughness contributes to the observed surface hydrophobicity with strong water droplet adhesion which approaches the petal effect. The contact angle of the droplet on the leaf surface was found to be 138°, and the droplet remained attached to the surface even when tilted at 180°. The occurrence of petal effect has mostly been confined to flower petals. Thus, the discovery of a similar wetting property on a leaf surface is potentially useful not only in the design of biomimetic surfaces but also in advancing our knowledge on biological surfaces. © 2016, Springer Science+Business Media New York.